Evaluation of varieties of different types of maize under organic farming - YADAV, S K; SHARMA, SHANTI KUMAR; CHOUDHARY, ROSHAN; JAT, GAJANAND; YADAV, M K; CHOUDHARY, RAM SWAROOP; JAIN, DEVENDRA; JAIN, RAVINDRA KUMAR; NAIK, B SRI SAI SIDDARTHA; DEVATWAL, PREETI (The Indian Journal of Agricultural Sciences, 2021)
Varietal evaluation of maize under organic input management provides protection against reduction in yield due to lack of suitable technology for growing potential varieties with organic inputs especially for plant nutrition supply. In this study 12 varieties of different types of maize comprising Hybrids, Sweet corn, Baby corn, Popcorn and Local were grown in southern west tribal part of Rajasthan, India for evaluation under organic system of plant nutrient management during kharif 2015-16. Sweet corn variety, Misty recorded significantly higher plant height at flowering during kharif 2015-16 (121.44 cm and 117.67 cm, respectively), maize hybrid variety T3 (PHM-3) recorded significantly higher dry matter accumulation at tasseling stage (83.33 g/plant & 81.00 g/plant, respectively) and sweet corn variety T4 (Sugar-75) recorded significantly higher leaf area index at silking stage (4.23 and 4.23, respectively) as compared to other varieties of different types of maize grown under organic system of plant nutrient management. During 2015 and 2016, variety T9 (VL-Amber of popcorn) recorded maximum maize equivalent yield (165.57 q/ha and 117.03 q/ha, respectively) and net return (₹ 218120/ha and ₹ 139741/ha, respectively).